The Role and Impact of Forensic Investigations Unit in the Fight Against Fraud, Corruption, Irregularities, Financial Misconduct and Maladministration in the Public Sector of South Africa - Tumiso D. Mokhomole (Khazanah Hukum, 2023)
This article examines the role and impact of the Forensic Investigations Unit in the fight against fraud, corruption, irregularities, financial misconduct and maladministration in the public sector of South Africa. Section 85(b) of the Public Finance Management Act, 1 of 1999 (PFMA) requires the Minister of Finance to craft regulations stipulating matters relating to the investigations of allegations of financial misconduct. The study adopted a qualitative research approach. Eight (8) participants from the Forensic Investigations Units of various state departments/ institutions were interviewed using open-ended questions. The study followed a purposive sampling guide as a participant were purposively selected. The study found that the role of the Forensic Investigations Unit in the public sector is to investigate the allegations of common law offences such as fraud, corruption, maladministration and financial irregularities. This Unit's impact is to reduce fraud and corruption incidents within the public sector and promote ethical public service through its recommendations. This study recommends amendments to the Public Service Act 1994 (PSA) and Part Three of the Public Service Regulations 2016 (PSR). The amendment is to fulfil the role of the Forensic Investigations Unit as part of a multi-anti-corruption agency in government departments/agencies. It is hoped to resolve reported allegations of fraud, corruption, irregularities and maladministration in the South African public sector quickly and effectively.